DINAMIKA SOSIAL PESANTREN DI INDONESIA - Fridiyanto Fridiyanto (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2020)
Pesantren is an authentic education of Indonesia. It has social politic dynamics in every periods. Pre Independence Period pesantrenis prohibited by colonial government the Netherlands. In Japan occupationperiod pesantren is annoyed by Japan. After independence 1945, in Old Order, pesantrenis accommodated by government, it is given budget of education. Pesantrens get problems in a time of New Order, Soehartothat is repressive for Islam society. Finally pesantren is assumed as social capital by government in Reform Era. Government concerns with pesantren through pro pesantren policy.